ANALISIS YURIDIS INFORMED CONSENT BRONKOSKOPI MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - R Dicky Wirawan L; Eddy Asnawi; Yelia Nathassa Winstar (Smart Education, 2026)
This research analyzes the regulation, legal obligations and juridical implications of implementing informed consent in bronchoscopy procedures following the enactment of Law Number 17 of 2023 concerning Health. As an invasive procedure in pulmonology, bronchoscopy carries significant inherent risks of complications, thus demanding the fulfillment of patient’s rights to comprehensive information as a condition for the legality of medical action. This normative legal research employs statutory and case approaches, utilizing primary, secondary and tertiary legal materials analyzed through qualitative descriptive methods. The results indicate that the 2023 Health Law strengthens informed consent as a two-way legal protection instrument, where Article 274 regulates patient’s rights to complete information and Article 293 provides administrative sanctions for violations. The legal obligations of medical personnel include providing evidence-based information, effective and documented communication and performing procedures according to professional standards and operational procedures. The juridical implications of non-compliance with informed consent are multi-layered, encompassing civil liability, disciplinary and ethical sanctions by the Indonesian Medical Disciplinary Honorary Council(MDHC) and potential criminal liability as an ultimum remedium. This research concludes that informed consent is not merely an administrative formality but the foundation of legality for bronchoscopy procedures, integrating clinical, ethical and juridical aspects. It is recommended to enhance the substantive communication process, specify documentation and strengthen clinical governance systems and medical law training in healthcare facilities.